Importance of Blue–Green Infrastructure in the Spatial Development of Post-Industrial and Post-Mining Areas: The Case of Piekary Śląskie, Poland - Iwona Kantor-Pietraga; Aleksandra Zdyrko-Bednarczyk; Jakub Bednarczyk (Land)
Post-industrial and post-mining areas are an important element of cities historically associated with industrial activity. The transformation of degraded areas is a challenge for spatial policy, which is characterized by a substantial impact on the cultural heritage of mining and industry. The case of Piekary Śląskie shows the consequences of deindustrialization, which leads to the degradation of urban space and requires innovative revitalization strategies considering the principles of sustainable development and the concept of blue–green infrastructure. Archived topographic maps and current interactive maps of the study city were used in a spatial data analysis. The aim was to determine the directions of the spatial development of post-industrial and post-mining areas using the example of a medium-sized city located in the core of the Katowice conurbation, while considering the role of blue–green infrastructure in the revitalization process. Integrating blue–green infrastructure into the city’s planning documents may serve as a model for other urban areas, highlighting the synergy benefits between urban development and environmental protection. Such solutions support the development of a green economy to improve residents’ living conditions and increase the city’s competitiveness in the region. The specific examples of the revitalization of the areas in the Andaluzja and Julian mines and the reclamation of the brickyard in the area of Kozłowa Góra in Piekary Śląskie show that a multifunctional approach to revitalization contributes to the harmonious development of urban spaces.